2023
DOI: 10.2147/jaa.s403286
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience on the Use of Mepolizumab from the Severe Asthma Registry of the German Asthma Net (MepoGAN-Study)

Abstract: Purpose The German Asthma Net (GAN) operates a Severe Asthma Registry that provides an overview of the clinical presentation and management of patients with severe asthma. Based upon data from the GAN registry, the MepoGAN study aimed to describe clinical profiles and treatment outcomes of patients who were treated with the anti-IL-5 monoclonal antibody mepolizumab (Nucala TM ) in routine practice in Germany. Patients and Methods The MepoGAN s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although these study requirements were designed to ensure accurate interpretation of the study results, they do not necessarily reflect real-world clinical practice; however, such restrictions on eligibility criteria would be expected in phase III trials of patients with severe asthma. Evidence from global and European observational/registry studies demonstrates that clinical benefit with mepolizumab in patients with severe asthma in real-world settings is consistent with randomised controlled trials [ 31 33 ]. In addition, like many clinical trial programmes conducted during the COVID-19 pandemic, this study experienced challenges in recruiting patients and conducting site visits.…”
Section: Discussionmentioning
confidence: 61%
“…Although these study requirements were designed to ensure accurate interpretation of the study results, they do not necessarily reflect real-world clinical practice; however, such restrictions on eligibility criteria would be expected in phase III trials of patients with severe asthma. Evidence from global and European observational/registry studies demonstrates that clinical benefit with mepolizumab in patients with severe asthma in real-world settings is consistent with randomised controlled trials [ 31 33 ]. In addition, like many clinical trial programmes conducted during the COVID-19 pandemic, this study experienced challenges in recruiting patients and conducting site visits.…”
Section: Discussionmentioning
confidence: 61%
“…Retrospective analyses also found consistent 50%-90% reductions in exacerbations and OCS requirements in less controlled settings [ 26 , 32 , 39 ]. The benefits have been confirmed across the spectrum of asthma severity and prior medication use [ 21 , 23 , 29 ]. The longer term real-world studies also found no loss of efficacy over one to three years [ 12 , 21 , 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…The benefits have been confirmed across the spectrum of asthma severity and prior medication use [ 21 , 23 , 29 ]. The longer term real-world studies also found no loss of efficacy over one to three years [ 12 , 21 , 41 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations